Pengaruh Penambahan Tulangan Bambu terhadap Kuat Lentur Panel Semen Eceng Gondok - Ahmad Fitri Sujatmiko; Sri Murni Dewi; Devi Nurlinah (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
This study is a follow-utilization of water hyacinth as a building material wall panel (Emen wall). From previous studies, physical properties, mechanical, acoustic and endurance burn this material meets the standards of building materials PUBI 1982 and ISO and ASTM C423-90a 03-6861.1-2002. In this study, the variable still is a variation of the test specimen without reinforcement with reinforcement of bamboo and bamboo in the form of a model variation of the beam section size (15x20cm) and sectional plates (5x15cm). While the independent variable is in the form of bending strength and deflection in the test specimen. The results showed the effect of bamboo reinforcement against bending strength cement panel hyacinth. On the test object model of the beam section with bamboo reinforcement ratio r = 0, r= 0.006 and r = 0.01 , powerful bending P = 24kg, P = 59kg and P = 72kg. To model the cross section of the plate with a bamboo reinforcement ratio r = 0, r = 0.017 and r = 0.025 , stronger bending is P = 3,33kg, P = 16,33kg and P = 21,83kg.